ORMDL3 overexpression facilitates FcεRI‐mediated transcription of proinflammatory cytokines and thapsigargin‐mediated PERK phosphorylation in RBL‐2H3 cells - Kazuhiro Ogi (Wiley, 2021)
Abstract Introduction The chromosomal region 17q21 harbors the human orosomucoid‐like 3 (ORMDL3) gene and has been linked to asthma and other inflammatory diseases. ORMDL3 is involved in the unfolded protein response (UPR), lipid metabolism, and inflammatory reactions. We investigated the effects of ORMDL3 overexpression in RBL‐2H3 cells to determine the contribution of ORMDL3 to inflammatory disease development. Methods We generated ORMDL3 stably overexpressing RBL‐2H3 cells to assess degranulation, transcriptional upregulation of interleukin‐4 (IL‐4), tumor necrosis factor‐α (TNF‐α), monocyte chemoattractant protein‐1 (MCP‐1), and mitogen‐activated protein kinase (MAPK) phosphorylation via FcεRI. In addition, we examined the effects of ORMDL3 overexpression on thapsigargin (TG)‐mediated proinflammatory cytokine transcription and UPR by monitoring MAPK, protein kinase‐like endoplasmic reticulum kinase (PERK), and inositol‐requiring enzyme 1 (IRE1) phosphorylation. Results Overexpression of ORMDL3 enhanced IL‐4, TNF‐α, and MCP‐1 expression after FcεRI cross‐linking, whereas the sphingosine‐1‐phosphate (S1P) agonist FTY720 suppressed this enhancement. There was no significant difference in degranulation and MAPK phosphorylation via FcεRI‐mediated activation between vector‐transfected and ORMDL3‐overexpressing cells. ORMDL3 overexpression accelerated TG‐mediated PERK phosphorylation, while MAPK phosphorylation and proinflammatory cytokine expression showed no significant changes in ORMDL3‐overexpressing cells. Conclusions Our findings suggest that ORMDL3 plays an important role in regulating proinflammatory cytokine expression via the S1P pathway and selectively affects the UPR pathway in mast cells.